Preservation of thalamic neuronal function may be a prerequisite for pain perception in diabetic neuropathy: A magnetic resonance spectroscopy study - Gandhi, Rajiv; Selvarajah, Dinesh; Sloan, Gordon; Greig, Marni; Wilkinson, Iain D.; Shaw, Pamela J.; Griffiths, Paul; Tesfaye, Solomon (Frontiers in Pain Research, 2023)
Introduction In this study, we used proton Magnetic Resonance Spectroscopy (1H-MRS) to determine the neuronal function in the thalamus and primary somatosensory (S1) cortex in different subgroups of DPN, including subclinical- and painful-DPN. Method One-hundred and ten people with type 1 diabetes (20 without DPN [no-DPN]; 30 with subclinical-DPN; 30 with painful-DPN; and 30 with painless-DPN) and 20 healthy volunteers, all of whom were right-handed men, were recruited and underwent detailed clinical and neurophysiological assessments. Participants underwent Magnetic Resonance Imaging at 1.5 Tesla with two 1H-MRS spectra obtained from 8ml cubic volume voxels: one placed within left thalamus to encompass the ventro-posterior lateral sub-nucleus and another within the S1 cortex. Results In the thalamus, participants with painless-DPN had a significantly lower NAA:Cr ratio (1.55+0.22 [mean ± SD]) compared to all other groups [HV (1.80±0.23), no-DPN (1.85±0.20), sub-clinical DPN (1.79±0.23), painful-DPN (1.75±0.19), ANOVA p<0.001]. There were no significant group differences in S1 cortical neurometabolites. Conclusion In this largest cerebral MRS study in DPN, thalamic neuronal dysfunction was found in advanced painless-DPN with preservation of function in subclinical- and painful-DPN. Furthermore, there was a preservation of neuronal function within the S1 cortex in all subgroups of DPN. Therefore, there may be a proximo-distal gradient to central nervous system alterations in painless-DPN, with thalamic neuronal dysfunction occurring only in established DPN. Moreover, these results further highlight the manifestation of cerebral alterations between painful- and painless-DPN whereby preservation of thalamic function may be a prerequisite for neuropathic pain in DPN.